Comparative Analysis of Bind Energies and Sites Between Simvastatin and Atorvastatin into CYP3A4 - Jiang, Tie-Chao; Kong, Ning; Zhao, Shan-Shan; Yang, Ping (Asian Journal of Chemistry, 2013)
The three-dimensional (3D) models of simvastatin and atorvastatin into CYP3A4 enzyme were constructed based on the crystal structure (PDB ID:3UA1) and refined by molecular dynamics simulations. The results showed that simvastatin and atorvastatin can stably bound into the active site of CYP3A4 enzyme. The hydrogen bonds and hydrophobic interactions played an important role in the stabilities of the conformation of the complexes. The interactions between simvastatin, atorvastatin and CYP3A4, as well as anchor amino acid residues for substrates binding were discussed. In addition, the potential dehydrogenated site by CYP3A4 of simvastatin and atorvastatin site was pointed out, which was in agreement with the experiment in vivo.